2016
DOI: 10.1111/sms.12782
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a single question to assess habitual physical activity of community‐dwelling older people

Abstract: Short running head:Single question on habitual physical activity 2 Validity of a single question to assess habitual physical activity of community-dwelling older peopleThe aim is to determine concurrent validity of a single self-report habitual physical activity (PA) question against accelerometer-based PA and mobility variables, and corresponding changes in self-reported PA and mobility. Cross-sectional and longitudinal data of the "Lifespace mobility in old age" (LISPE) cohort and its substudy on PA were uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…However, even though self-reports may both over-or underestimate the actual amount of physical activity, 42 even a single question could be a useful method to estimate physical activity. 43 The present study provided some interesting findings regarding motivational and volitional characteristics and RT continuation. Firstly, contrary to previous research, 15,18 the level of the characteristics was not related to RT continuation.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, even though self-reports may both over-or underestimate the actual amount of physical activity, 42 even a single question could be a useful method to estimate physical activity. 43 The present study provided some interesting findings regarding motivational and volitional characteristics and RT continuation. Firstly, contrary to previous research, 15,18 the level of the characteristics was not related to RT continuation.…”
Section: Discussionmentioning
confidence: 56%
“…obtained information regarding gym visits from the fitness center and found that only 20% of participants continued RT during a 4‐month follow‐up and none of them met the recommended twice‐a‐week frequency. However, even though self‐reports may both over‐ or underestimate the actual amount of physical activity, even a single question could be a useful method to estimate physical activity …”
Section: Discussionmentioning
confidence: 99%
“…Current level of leisure‐time physical activity (PA) was assessed by a questionnaire with a seven‐point scale ranging from household chores to competitive sports . A similar scale has been validated against accelerometer‐based physical activity and mobility variables . Specifically, the response categories were (1) no activity exceeding activities of daily living, (2) light walking or outdoor activity one to two times per week, (3) light walking or outdoor activity several times per week, (4) brisk physical activity causing some decree of sweating and breathlessness one to two times per week, (5) brisk physical activity causing some degree of sweating and breathlessness several times per week, (6) physical activity causing sweating and rather strong shortness of breath several times per week, and (7) competitive sports and related training.…”
Section: Methodsmentioning
confidence: 99%
“…Self-reported physical activity was assessed using a seven-point scale combining frequency and intensity of common physical activities [26]. Participants were categorized into at most light physical activity (at most light housework or gardening and short walks once or twice a week), moderate physical activity (at least moderate physical activity <3 h/week), and regular physical activity (moderate physical activity ≥4 h/week or strenuous physical activity).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were categorized into at most light physical activity (at most light housework or gardening and short walks once or twice a week), moderate physical activity (at least moderate physical activity <3 h/week), and regular physical activity (moderate physical activity ≥4 h/week or strenuous physical activity). The self-reported physical activity scale and its categorization have shown to have concurrent validity with accelerometer assessed step counts and different measures of mobility [26]. …”
Section: Methodsmentioning
confidence: 99%